Indonesian Foreign Policy In Maintaining Multilateral Relations of ASEAN Members - Abdurofiq, Atep; Putra, Gilang Rizki Aji; Yunus, Nur Rohim (BULETIN ADALAH, 2024)
Indonesia's foreign policy remains consistent, adhering to free and active diplomacy principles grounded in Pancasila and the 1945 Constitution. The Indonesian foreign policy is characterized by its autonomy and proactivity, maintaining a neutral stance while consistently adapting to the ever-changing dynamics of world politics. Independently shape perspectives on global issues without being bound by military might or alliances, and actively promote peace, justice, camaraderie, and mutually advantageous collaboration among states. Indonesia continues to regard ASEAN as the primary foundation of its foreign strategy. Hence, this article seeks to elucidate Indonesia's foreign policy towards ASEAN, the collaborative relations between Indonesia and ASEAN member states, and the outcomes of their cooperation in fostering political stability in Southeast Asia. The conclusion asserts that Indonesia's foreign policy remains committed to the principle of free and active engagement with ASEAN and endeavours to uphold the stability of multilateral relations among ASEAN member nations.